A comparative study of laying open of wound vs primary closure in low fistula in ano - Garag, Sushila; Nagur, Basavaraj (International Surgery Journal, 2019)
Background: Perianal fistulas remain a surgical treatment challenge in colorectal practice due to high recurrence rates and the risk of postoperative wound infection and incontinence. Anal fistula represents one of the most frequent anorectal diseases. Methods: This is a randomized comparative prospective study of 30 cases of fistula-in-ano presenting at the surgical OPD of Almeen Medical College and Research Institute from 1 September 2017 to 31 june 2018. Results: In our study the age of the patient varied from 25-60 years, patient’s wound healed in 3-4 weeks in those who underwent open fistulectomy, whereas in the primary closure method the wounds healed in 1-2 weeks. Recurrence of fistula occurred in 5 patients. Conclusions: The primary closure method of fistulectomy is a safe and feasible method and more effective in the management of fistula-in-ano.